Heat transfer of nanofluid through boundary layer stagnation flow over shrinking surface influencing injection and variable stream conditions - Balachandar, VibhuVignesh (2015)
In this paper, we analysed convective boundary layer stagnation point flow of nanofluid influencing by injectionand magnetic field over a porous shrinking surface is investigated numerically and simulated with Maple 18 Software. Thermophoresis and Brownian motion effects are included in the nanofluid model.Governing nonlinear boundary layer equations for momentum, energy and continuity equations are transformed into a system of nonlinear ordinary coupled differential equations by using similarity transformations. The effects of physical parameters on nanofluid (Water and Gaseous) are analysed. It is found that for a certain range of injection process, solutions exists for velocity flow, temperature flow and volume concentration. It tends to provide solutions for skin friction, rate of heat and rate of mass transfer of nanofluids (Water and Gaseous).